Length-dependent toxicity of TiO2 nanofibers: mitigation via shortening. Issue 4 (20th April 2020) - Bianchi, Massimiliano G.; Campagnolo, Luisa; Allegri, Manfredi; Ortelli, Simona; Blosi, Magda; Chiu, Martina; Taurino, Giuseppe; Lacconi, Valentina; Pietroiusti, Antonio; Costa, Anna L.; Poland, Craig A.; Baird, Daniel; et al.
Abstract: Length and aspect ratio represent important toxicity determinants of fibrous nanomaterials. We have previously shown that anatase TiO2 nanofibers (TiO2 NF) cause a dose-dependent decrease of cell viability as well as the loss of epithelial barrier integrity in polarized airway cell monolayers. Herein we have investigated the impact of fiber shortening, obtained by ball-milling, on the biological effects of TiO2 NF of industrial origin. Long TiO2 NF (L-TiO2 NF) were more cytotoxic than their shortened counterparts (S-TiO2 NF) toward alveolar A549 cells and bronchial 16HBE cells. Moreover, L-TiO2 NF increased the permeability of 16HBE monolayers and perturbed the distribution of tight-junction proteins, an effect also mitigated by fiber shortening. Raw264.7 macrophages efficiently internalized shortened but not long NF, which caused cell stretching and deformation. Compared with L-TiO2 NF, S-TiO2 NF triggered a more evident macrophage activation, an effect suppressed by the phagocytosis inhibitor cytochalasin B. Conversely, a significant increase of inflammatory markers was detected in either the lungs or the peritoneal cavity of mice exposed to L-TiO2 NF but not to S-TiO2 NF, suggesting that short-term macrophage activation in vitro may not be always a reliable indicator of persistent inflammation in vivo . It is concluded that fiber shortening mitigates NF detrimental effects on cell viability and epithelial barrier competence in vitro as well as inflammation development in vivo . These data suggest that fiber shortening may represent an effective safe-by-design strategy for mitigating TiO2 NF toxic effects.